The shared epitope phenomenon—A potential impediment to virtual crossmatch accuracy. Issue 8 (14th June 2020) - Garcia‐Sanchez, Cynthia; Usenko, Crystal Y.; Herrera, Nancy D.; Tambur, Anat R.
Abstract: With the implementation of the new kidney allocation system (KAS), there is increased reliance on a virtual crossmatch/histocompatibility risk assessment (vXM) for evaluating potential presence, as well as strength, of HLA antibodies against a potential donor. The accuracy of such an assessment depends on the precision in the identification of the recipient's antibody profile and the potential donor's HLA typing. While the development of the single antigen bead (SAB) multiplex assay has improved the sensitivity and specificity of HLA antibody detection, several limitations of the assay (specific to certain sensitized patients) can complicate accurate interpretation of results. In this report, we focus on the "shared‐epitope" phenomenon, a condition in which antibody strength can be underrepresented, or its presence completely missed, due to binding of the antibody to competing targets on multiple antigens (beads), effectively "diluting" the resulting MFI readout. Here, we provide a relevant background to understand this phenomenon and present a couple of case studies illustrating how it can be investigated, leading to a more accurate histocompatibility consultation.